1966
DOI: 10.1021/jm00322a032
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinostatic Activity of Thiosemicarbazones of Formyl Heteroaromatic Compounds.1 III. Primary Correlation

Abstract: Thiosemicarbazciiies of 41 formyl heterocycles and two heterocyclic ketones were prepared and tested on four mouse tumor systems. The variables studied included: 16 ring systems, different positions of attachment of the formyl group relative to the ring heteroatoms, additional ring substituents, and terminal substituents in the thiosemicarbazone side chain. The minimum requirement for act,ivity is formyl group attachment to a ring carbon CY to an uneiicumbered ring nitrogen of heteroaromatic character. The T-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
4

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 0 publications
4
66
0
4
Order By: Relevance
“…(Nandi, Chaudhuri, Mazumdar & Ghosh, 1984a,b;Cavalca, Nardelli & Fava, 1962). These compounds have exhibited antibacterial, antiviral, carcinostatic or carcinogenic activities (Johnson, Joyner & Perry, 1952;French & Blanz, 1965Williams, 1972;Erturk, Morris, Cohen, Von Esch, Crovetti, Price & Bryan, 1971;Jensen & Jensen, 1952). It has been suggested that the biological activities of these compounds are due to their capability to form metal complexes (Kirschner, Wei, Francis & Bergrnan, 1966;Palenik, Rendle & Carter, 1974).…”
Section: C12h9c1n2osmentioning
confidence: 99%
“…(Nandi, Chaudhuri, Mazumdar & Ghosh, 1984a,b;Cavalca, Nardelli & Fava, 1962). These compounds have exhibited antibacterial, antiviral, carcinostatic or carcinogenic activities (Johnson, Joyner & Perry, 1952;French & Blanz, 1965Williams, 1972;Erturk, Morris, Cohen, Von Esch, Crovetti, Price & Bryan, 1971;Jensen & Jensen, 1952). It has been suggested that the biological activities of these compounds are due to their capability to form metal complexes (Kirschner, Wei, Francis & Bergrnan, 1966;Palenik, Rendle & Carter, 1974).…”
Section: C12h9c1n2osmentioning
confidence: 99%
“…The antibacterial, antiviral and anticancer activities possessed by substituted thiosemicarbazides and thiosemicarbazones have generated rapidly growing interest in the chemical, biochemical and structural aspects of these compounds (Johnson, Joyner & Perry, 1952;French & Blanz, 1966;Agrawal, Booth & Sartorelli, 1968;Agrawal, Cushley, McMurray & Sartorelli, 1970;Williams, 1972;Agrawal, Booth & Sartorelli, 1973;Kuroda, Neidle & Wilman, 1984). It has been suggested that the biological activities of these groups of N,S donor ligands originate from their metal-chelating and reductive capacities (Kirschner, Wei, Francis & Bergman, 1966;Palenik, Rendle & Carter, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…For example, acetone thiosemicarbazone (ATSC) has no known biological activity while Hagenbach & Gysin (1952) reported that 4-formylpyridine thiosemicarbazone has some antitubercular activity. French & Blanz (1966) found that e-(N)-formyl heteroaromatic thiosemicarbazones have antitumor activity but their toxicity has limited their clinical usefulness. However, Blanz & French (1968) found that 5-hydroxy-2-formylpyridine thiosemicarbazone, henceforth 5-OH-2FPTSC, had a much lower toxicity while still retaining favorable antitumor activity.…”
Section: Introductionmentioning
confidence: 99%